Dopad environmentální politiky na činnost malých a středních podniků - Hornungová, Jana; Klímková, Markéta (Univerzita Pardubice, 2011)
In the last years, the corporate governance has achieved the large development. All businesses must adapt to market development and the related economic development. Modern trends in society call for improving the quality and adapting to the surroundings of the enterprises because of their competitiveness. This is the driving power of innovation in all enterprises. One of these new trends is the environmental policy that adapts activities of enterprises to environmental protection, which is one of the important factors of success. From the perspective of environmental policy and its impact on enterprises is necessary to target activities to comply with environmental requirements. The following article describes the impact of environmental policy to the activities of small and medium-sized enterprises, which have the same responsibilities of environment like the other major companies. The article includes research of the questionnaire method. The analysis of the questions in the questionnaire shows us the current position and relationship to the environment for SMEs. Respondents were small and medium-sized enterprises in the Czech Republic.
Keywords: small – sized enterprises; medium – sized enterprises; environmental policy; company